The New Economic Policy and Further Marginalisation of the Indians - K. Anbalakan (Kajian Malaysia, 2003)
The two fundamental objectives of the New Economic Policy (NEP) were the eradication ofpoverly irrespective ofrace and the restructuring ofthe society so as to eliminate the identification of a race with its economic functions, a legacy of the colonial times. The eradication of poverty and the restructuring of society, it was argued, would help foster national unity - the overriding objective of the whole policy. These objectives were to be achieved by redistributing the wealth of the nation equitably among all the major races. Thus, in twenty years, it was estimated that the bumiputera should be enjoying a 30 percent stake and the nonbumiputera 40 percent leaving the remaining 30 percent for the foreigners. Promises were made to the effect that no one race would be unduly discriminated against in pursuing these objectives and all would benefit as the economy was expected to grow with the implementation of the NEP (Mid Term Review, Second Malaysia Plan [MTR-2MP 1973: 85-871). This assurance gave the Indian community, which at that time was holding a miserable one percent stake in the nation's economic wealth, some hope about its future economic position. However, in 1990, when the NEP officially came to an end, the community's stake remained stagnated at one percent. The National Development Policy (NDP) and the National Vision Policy (NVP), which were formulated thereafter, too, did not improve any significantly the Indian community's economic position. This article analyses the position of the Indian community under the NEP.